PENGARUH TINGKAT PROFITABILITAS, UKURAN PERUSAHAAN, KEPEMILIKAN SAHAM OLEH PUBLIK, LEVERAGE DAN KELOMPOK INDUSTRI TERHADAP TINGKAT INTERNET FINANCIAL REPORTING (IFR) - Abdul Rozak (STMIK Mardira Indonesia, Bandung, 2015)
Internet Financial Reporting (IFR) becomes an important trend in line with the development of internet technology. Companies can store financial information via the Internet to reach a wider audience and worldwide, faster and cheaper. This study sought to examine the practice of Internet Financial Reporting (IFR) and analyze the factors that influence it. Samples were companies that belong to the calculation of LQ-45 in 2012. The samples were taken by purposive sampling, in order to obtain adequate samples for the study were 39 Company LQ-45. The technique of analysis using multiple linear regression analysis. While the hypothesis used to test the results of the partial (t test) and simultaneous (F test). The results of this study indicate that the factor profitability and firm size have a significant effect on the practice of Internet Financial Reporting (IFR). However, other factors, such as: public ownership, leverage and industry groups did not significantly affect the practice of Internet Financial Reporting (IFR). Keywords: Profitability, Company Size, Public Shareholding, Leverage, Industrial Group